Characterisation of volatile compounds of farmed soft‐shelled turtle (Pelodiscus sinensis) by solid‐phase microextraction and the influence of matrix pH on the release of volatiles. (24th November 2016) - Xu, Yanqun; Limwachiranon, Jarukitt; Li, Li; Ru, Qiaomei; Luo, Zisheng
Summary: Although farming and consuming of soft‐shelled turtle has been practised for centuries, the aroma‐impact compounds in the meat have not been determined. Furthermore, matrix pH, usually changing during processing and storage stage, was rarely investigated for the influence on volatile profiles. To these aims, soft‐shelled turtle meat was subjected to different pH conditions and the potential volatile compounds were analysed under different extraction conditions by headspace solid‐phase microextraction (HS‐SPME). A total of forty‐three volatiles were identified; in which, nonanal, (E, E)‐2, 4‐heptadienal, octanal, decanal, hexanal, (E)‐2‐nonenal, heptanal, 1‐octen‐3‐ol and o‐xylene were assigned as aroma‐impact compounds by high relative odour activity value (ROAV). Overly basic or acidic pH significantly ( P  <   0.05) facilitated the release of volatiles under moderate extraction conditions. The total volatilisation increased by 30.1% to 298% in pH‐shifted samples, while the highest one was found in pH 2 or pH 11. However, the results of principal components analysis (PCA) demonstrated that increased extraction time or temperature hindered the pH enhancement. Abstract : The aroma‐impact volatile compounds of farmed soft‐shelled turtle ( Pelodiscus sinensis ) and the interaction between pH and SPME conditions on their release.